The Role of Trader Psychology in Enhancing Forex Trading Profitability Through Technical Analysis, Fundamental Analysis, and Risk Management at Wijaya Trading Community Indonesia - Sumadi Sumadi; Arik Susbiyani; Astrid Maharani (Lembaga Penelitian dan Pendidikan (LPP) Kalibra, 2026)
Retail forex and commodity trading in Indonesia has grown rapidly, with active retail investors exceeding 901,000 in 2025 (OJK, 2025), yet between 74% and 89% of retail trading accounts continue to incur net losses globally (ESMA, 2018; FCA, 2023; ASIC, 2022). This performance gap indicates that trading profitability is not solely determined by analytical competence, but critically conditioned by the psychological state of the trader at the moment of decision execution. This study examines the mediating role of Trader Psychology between Technical Analysis, Fundamental Analysis, and Risk Management and Trading Profitability among 250 active members of Wijaya Trading Community Indonesia. Using a quantitative explanatory approach with PLS-SEM analysis through SmartPLS 4.1.1.8, data were collected via a structured 25-indicator five-point Likert-scale questionnaire and analysed using 5,000-subsample BCa bootstrapping at the 95% confidence level. All eight hypotheses were supported. The structural model demonstrated substantial predictive power with R² = 0.791 for Profitability and R² = 0.682 for Trader Psychology. Trader Psychology was the strongest direct determinant of Trading Profitability (β = 0.329, p < 0.001), while Technical Analysis was the sole independent variable with a significant direct path to profitability (β = 0.214, p = 0.001). Risk Management generated the largest indirect effect through Trader Psychology (IE = 0.101, BCa CI [0.047; 0.159]), demonstrating full mediation, followed by Fundamental Analysis (IE = 0.091) and Technical Analysis (IE = 0.083, partial mediation). These findings establish trader psychology as the critical psychological bridge between analytical competencies and realised profitability, and introduce the Integrated Trading Competency Model (ITCM) as a novel framework for trader development. Training programmes, broker education mandates, and regulatory frameworks particularly OJK and BAPPEBTI — should systematically integrate psychological development alongside technical and risk management instruction.